Varietal response of cassava root yield components and root necrosis from cassava Brown streak disease to time of harvesting in Uganda - Kanju, E.; Uzokwe, Veronica N.E.; Ntawuruhunga, P.; Tumwegamire, Silver; Yabeja, J.; Pariyo, A.; Kawuki, R.S. (Elsevier, 2019)
Cassava brown streak disease (CBSD) is the most important biotic constraint threatening cassava (Manihot esculenta Crantz) production in eastern and southern Africa, and the food and income security of millions of rural farmers. With no tangible solution in view, farmers cope with the disease by harvesting the crop early, a practice that also leads to yield losses owing to small root size. This study evaluated CBSD root necrosis (RN), the total fresh root yield (TFRY), percentage marketable fresh root yield (PMFRY) and dry matter content (DMC) of six cassava varieties (MM, 2006/90, MM, 2006/123, MM, 2006/128, MM, 2006/130, MM 96/4271, and TME14) at different times of harvesting after the recommended 12 months after planting (MAP). Trials were planted during April 2012 at Sendusu and Serere located in the Wakiso and Serere districts of Uganda, respectively. The two sites are distinct in climatic, soil and CBSD disease pressure conditions. A split-plot design was used with cassava varieties as the main plots and times of harvesting (12, 16, 20 and 24 MAP) as sub-plots. Highly significant differences (P ≤ 0.001) were detected between sites (S), varieties (V) and time of harvesting (T) for TFRY, PMFRY and RN, whereas only V effects were highly significant (P ≤ 0.001) for DMC. The V × S interactions were highly significant for TFRY, PMFRY and RN, while the V × T interactions were highly significant for PMFRY and significant (P ≤ 0.01) for TFRY and DMC. The PMFRY decreased by about 14–27% as the plants remained in the field after 12 MAP. There was a great difference among clones, depending on location. Variety MM 2006/128 performed the best, with virtually no root damage even at 24 MAP at both sites. The mean CBSD root necrosis severity score among the varieties at each site increased from 2.6 (at 12 MAP) to 3.1 (at 24 MAP) at Sendusu, and from 1.9 (at 12 MAP) to 2.4 (at 24 MAP) at Serere. However, for MM2006/128 which was the best performing variety, the root necrosis score remained about 1.0 at Sendusu and about 1.3 at Serere. Time of harvesting had no significant effect on DMC. This study showed it is possible to breed new cassava varieties that combine tolerance to CBSD with long periods of in-ground storability. Genotype and environment had a profound effect on all the traits analysed, suggesting that genotypes should be selected for specific environments and harvest times. The results indicate that some of the clones (MM, 2006/128, MM, 2006/123 and MM, 2006/130) investigated in this study will be useful in the fight against CBSD in the region especially for the mid-altitude areas, which have recently been seriously affected by the virus disease.